TINGKAT AKURASI APLIKASI AZIMUTH MATAHARI PADA GOOGLE PLAY STORE (Analisis Perbandingan Rasd al-Qiblah Harian Sistem Hisab Data Ephemeris dan Software Hisab Komputer) - Kasim, A. Jusran (ELFALAKY: Jurnal Ilmu Falak, 2020)
The direction of the Qibla is legitimate prerequisite of prayer for all Muslims without exception in carrying out the worship. Thus, it is an obligatory for the communities to be informed about the Qibla direction. Constantly the sun is in the parallel position to the azimuth Qibla of particular areas with the term of ras}d al-qiblah. Finding out the moment is fairly apparent. It is by installing the sun azimuth data application which is eventually used as a benchmark to know the occurrence of ras}d al-qiblah daily. Currently, solar azimuth data applications are frequently found on Google Playstore application. Regarding to this, researchers intended to test the accuracy of the application offered by Google Playstore. Hence, subsequently it will be able to be classified which application with high level of accuracy. By using the comparative analysis method, the researchers tested the azimuth results obtained in mobile phone application by comparing the results of the computer software application and the results of the daily ras}d al-qiblah ephimeris data system. Based on the study results, it was found that the results obtained in computer and mobile phone applications were relatively the same when rounding the values with manual computation of the daily ras}d al-qiblah ephemeris data system. However, it was depicted a single application which was slightly different where the scale was one arc unit degree. The application evaluation is proximately aimed at assisting the society especially university or college students and practitioners in filtering out the precise application which is able to be used as guidelines in determining the daily rasyd al qiblah. Keywords: Azimuth, aplikasi, playstore, rasd al-qiblah